Study of the genus Bracon Fabricius, 1804 (Hymenoptera: Braconidae) of Southern Iran with description of a new species - Ameri, Ali; Talebi, Ali Asghar; Beyarslan, Ahmet; Kamali, Karim; Rakhshani, Ehsan (Zootaxa, 2014)
A survey on the genus Bracon Fabricius, 1804 was conducted in Hormozgan province, Southern Iran, during February 2011–July 2012. In all, 19 species belonging to seven subgenera were collected and identified, of which seven species and the subgenus Asiabracon Tobias, 1957 are recorded for first time from Iran. Bracon (Orthobracon) persiangulfensis Ameri, Beyarslan & Talebi sp. n. is newly described and illustrated from the Queshm island of Persian Gulf. Morphological characters of the new species were compared with the congeneric species. The newly recorded species from Iran were as follow: B. (Asiabracon) quardrimaculatus Telenga, 1936; B. (Bracon) kozak Telenga, 1936; B. (Glabrobracon) immutator Nees; B. (Habrobracon) telengai (Mulyarskaya, 1955); B. (Habrobracon) variegator Spinola, 1808; B. (Orthobracon) epitriptus Marshall, 1885 and B. (Orthobracon) exhilarator Nees, 1834. A key is presented for identification of Bracon species collected in Hormozgan province as well as an updated checklist of all Bracon species occurring in Iran.